Teachers’ Innovation in Teaching English during The Covid-19 Pandemic - Emiliasari, Raynesa Noor; Syarifah, Eva Fitriani; Furqon, Ijan Saeful (International Journal of Contemporary Studies in Education, 2022)
The Covid-19 pandemic is a tragedy that grieves the entire population of the earth. All segments of human life on earth are disturbed, education is no exception. Many countries closed schools, universities, including Indonesia. This study aims to reveal (1) the learning innovations teachers’ developed by teachers in learning English during the pandemic (2) the obstacles teachers' encountered during learning English during the Covid-19 pandemic. This is a qualitative descriptive research design; the instruments are interviews and questionnaires. The results showed that the learning innovations developed by teachers during the pandemic were zoom meetings, WhatsApp and hybrid learning is a learning method that combines or combines online learning with face-to-face learning (PTM). Meanwhile Obstacles faced by teachers in using zoom meeting and WhatsApp were the internet issue students who do not affordances learning media facilities smart phones and laptops. This study may suggest teachers' to use the application media which is more exciting and interesting, furthermore the development of facilities to support teaching and learning using application media must be improved.